1993
DOI: 10.1038/sj.bdj.4808166
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontics in the general dental service of England and Wales: a critical assessment of standards

Abstract: Out of a sample of 1210 orthodontic patients treated within the General Dental Services in England and Wales, a high proportion showed no improvement. Upper and lower fixed appliances had the greatest influence on the outcome of treatment in terms of aesthetics, dental health need and standards. When treatment was analysed according to the appliance used, there were no statistically significant differences in the standard of treatment undertaken by specialist orthodontists and general dental practitioners. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 0 publications
2
49
0
4
Order By: Relevance
“…The 1987-88 study 3 and the earlier of these two papers, 8 showed that orthodontic qualification was not a factor in measures of outcome on a national scale, once appliance type was included in the analysis. It is interesting, however, that these results identify orthodontic qualification as quite a strong predictor of fixed appliance use, and in particular, of dual arch fixed appliance use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1987-88 study 3 and the earlier of these two papers, 8 showed that orthodontic qualification was not a factor in measures of outcome on a national scale, once appliance type was included in the analysis. It is interesting, however, that these results identify orthodontic qualification as quite a strong predictor of fixed appliance use, and in particular, of dual arch fixed appliance use.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain the apparent disparities between this and earlier studies on outcome. 3,8,10 While it is likely that some practitioners can gain a degree of proficiency with fixed appliance techniques after short courses, or a few perhaps by private study alone, most would be more competent and confident in their use after a period of practise under a mentor. The need for more practitioners who have been trained on formal postgraduate courses is therefore underlined as an important factor in any future improvement of GDS orthodontics.…”
Section: Discussionmentioning
confidence: 99%
“…Appliance selection is the main criterion in outcome, [1][2][3][4][5][6]8 but those who have had a formal training in orthodontics are more likely to use fixed appliances. Where other practitioners had learned to use these appliances, whether on short courses, clinical assistant attachments, or indeed, perhaps when they were self-taught, their results appeared to have been similar to those attained by orthodontic diplomates or members.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate choice of appliances has been suggested to be of particular importance. 7,8 Generally, regardless of the sphere of practice considered and of other factors involved, dual arch fixed appliances have been shown to be the most reliable, [3][4][5][6]8 whilst single arch fixed appliance treatments tend to be more effective than those involving only removable appliances. 5,6 Appliance type was shown to over ride differences due to hospital grade of operator and individual hospital departments.…”
Section: Appliance Types Investigatedmentioning
confidence: 99%
See 1 more Smart Citation